Impact of tuberculosis exposure at home on mortality in children under 5 years of age in Guinea-Bissau. Issue 2 (8th December 2010) - Gomes, Victor F; Andersen, Andreas; Wejse, Christian; Oliveira, Ines; Vieira, Fina J; Joaquim, Luis Carlos; Vieira, Cesaltina S; Aaby, Peter; Gustafson, Per
Abstract : Objective: To assess mortality related to exposure to tuberculosis (TB) at home among children in urban areas of Guinea-Bissau. Methods: In four suburban areas included in the demographic surveillance system of the Bandim Health Project in Bissau, the mortality of children aged <5 years living with an adult with TB was compared with the mortality of children in the general population. Results: Children <5 years of age exposed to an adult with intrathoracic TB had 66% higher mortality than unexposed children (HR 1.66, 95% CI 1.2 to 2.3). The risk was higher for children living in the same family as a TB case (HR 2.15, 95% CI 1.3 to 3.7) than for children living in the same house but not belonging to the same family as the TB case (HR 1.51, 95% CI 1.0 to 2.2). For children whose mother had TB, mortality was increased eightfold (HR 7.82, 95% CI 2.1 to 30). The risk of death was particularly increased from 6 months following exposure (HR 2.16, 95% CI 1.5 to 3.2) and the highest rate of excess mortality was found in children aged 3–4 years. Excess mortality was highest among children with close contact with an adult with sputum-positive pulmonary TB (HR 1.90, 95% CI 1.1 to 3.2), but contact with a sputum-negative case was also associated with increased mortality (HR 1.55, 95% CI 1.0 to 2.3). Adjusting for potential confounding factors did not change these results. The mortality among children living in the same houses 3 years earlier was not increased (HR 0.90, 95% CI 0.6 to 1.3). Conclusion: Intimate family contact with a TB case represents a significant risk factor for child mortality in a low-income country.